Comparative analysis of gene expression in normal and cancer human prostate cell lines - E. E. Rosenberg; G. V. Gerashchenko; V. I. Kashuba (The Ukrainian Biochemical Journal, 2014)
Prostate cancer is one of the main causes of mortality in men with malignant tumors. The urgent problem was a search for biomarkers of prostate cancer, which would allow distinguishing between aggressive metastatic and latent tumors. The aim of this work was to search for differentially expressed genes in normal epithelial cells PNT2 and prostate cancer cell lines LNCaP, DU145 and PC3, produced from tumors with different aggressiveness and metastatic ability. Such genes might be used to create a panel of prognostic markers for aggressiveness and metastasis. Relative gene expression of 65 cancer-related genes was determined by the quantitative polymerase chain reaction (Q-PCR). Expression of 29 genes was changed in LNCaP cells, 20 genes in DU145 and 16 genes in PC3 cell lines, compared with normal line PNT2. The obtained data make it possible to conclude that the epithelial-mesenchymal cell transition took place, which involved the loss of epithelial markers, reduced cell adhesion and increased migration. We have also found few differentially expressed genes among 3 prostate cancer cell lines. We have found that genes, involved in cell adhesion (CDH1), invasiveness and metastasis (IL8, CXCL2) and cell cycle control (P16, CCNE1) underwent most changes. These genes might be used for diagnosis and prognosis of invasive metastatic prostate tumors.